Development of Lentil Aquafaba-Based Food Emulsions with Xanthan Gum or Pregelatinized Corn Starch as Stabilizers - Valentyna Dehtiar; Anastasiia Sachko; Anna Radchenko; Olha Hrynchenko; Sergey Gubsky (Biology and Life Sciences Forum, 2025)
Currently, there is an increasing trend towards the use of legumes aquafaba-based emulsions for food applications. In this study, emulsions containing 30 and 60% sunflower oil with lentil aquafaba (LA) were developed, and xanthan or pregelatinized corn starch were added as stabilizers. Preliminary studies of lentil technological properties enabled the optimization of aquafaba production, achieving a dry matter content of 5.5% and a protein concentration of 1.1%. Emulsions with 0.5 and 0.8% aquafaba lentil protein without and with the addition of xanthan gum (0.1 and 0.2%) or starch (1 and 2%) were studied. Increasing the xanthan and starch content resulted in an increase in the average droplet size for emulsions with 30% oil and a decrease in the values for emulsions with 60% oil. For emulsions with a lower oil content, there was a visual instability over time with the addition of starch, which led to emulsion degradation. Rheological studies made it possible to classify the samples as a non-Newtonian fluid with a pseudoplastic flow pattern. The stability of the emulsions was observed due to an increase in the viscosity of the continuous phase due to the inclusion of the stabilizer. The influence of the nature of the stabilizer on this process is confirmed by calculations using various rheological models. Food emulsions obtained using lentil aquafaba are a promising ingredient in the development of emulsion food formulations.